VD_FINDINFO AM 45/16 - 5/2017 vom 23. Januar 2017 - VD Tribunal cantonal (2017)
AFFECTION DENTAIRE, OPÉRATION DU SHUNT, LIEN DE CAUSALITÉ, FORCE PROBANTE, EXPERTISE MÉDICALE | 31 al. 1 LAMal, 19a OPAS